DESIGN ELEMENTS AND DESIGN PRINCIPLES IN THE JABUBOLON AT MEAT TOURISM VILLAGE, TOBA DISTRICT - Setiawan, Emily (Ide dan Dialog Desain Indonesia (Idealog), 2024)
The traditional architecture of Batak Toba is one of tourism attractions, tourismsector is oneof drivers of country's economy. The government's ef orts to enhance this sector with "5 Super PriorityDestinations" programe, one of them is Lake Toba area in North Sumatra. The Meat TourismVillage is part of its development in cultural field and done revitalization of traditional buildings, including the Jabu Bolon. Revitalization have increased tourist visits, but it hasn't been accompanied by utilization of cultural value andarchitectural richness of local Batak Toba traditional architecture in tourism infrastructure. The objectiveof the study is to identify design elements and principles that shape the main traditional building there, JabuBolon. The study found 7 design elements and 16 design principles contribute shaping Jabu Bolon inMeat Tourism Village. Keywords : traditional architecture, batak toba, design element, design principle, Meat TourismVillage.